2019
DOI: 10.1088/1361-6463/ab070a
|View full text |Cite
|
Sign up to set email alerts
|

Special issue on spin caloritronics

Abstract: View the article online for updates and enhancements. Recent citationsDetermining absolute Seebeck coefficients from relative thermopower measurements of thin films and nanostructures S. J. Mason et al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…11 and 12 I graphically summarize the central effects in what has become known as spin caloritronics. [17][18][19][20]133] One of the original concepts that drove interest in spin caloritronics is the idea that the spin up and spin down electrons in a ferromagnetic metal could have different Seebeck coefficients, such that applying a thermal gradient to the FM metal could generate a difference in spin potential that could provide a source of pure spin currents. This effect can be realized, but it has now been conclusively shown that the spin separation can only exist on a quite short length scale comparable to the spin diffusion length [134] in the metallic ferromagnet, λ FM .…”
Section: Spin Caloritronic Effects: Interfaces and Magnonsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 and 12 I graphically summarize the central effects in what has become known as spin caloritronics. [17][18][19][20]133] One of the original concepts that drove interest in spin caloritronics is the idea that the spin up and spin down electrons in a ferromagnetic metal could have different Seebeck coefficients, such that applying a thermal gradient to the FM metal could generate a difference in spin potential that could provide a source of pure spin currents. This effect can be realized, but it has now been conclusively shown that the spin separation can only exist on a quite short length scale comparable to the spin diffusion length [134] in the metallic ferromagnet, λ FM .…”
Section: Spin Caloritronic Effects: Interfaces and Magnonsmentioning
confidence: 99%
“…The latter approach, using existing thermal gradients or intentionally created thermal gradients to manipulate the spin degree of freedom in a magnetic system, has grown into its own very active sub-field of spin caloritronics. [17][18][19][20] The goal of this review is first to provide a simple and accessible motivation for the importance of thermal effects in spintronic materials and devices, focusing on model systems and calculations that demonstrate the important fundamentals that often arise. The models demonstrating the fundamentals of thermal gradient generation and direction will point to the importance of understanding the "zoo" of thermoelectric and magneto-thermoelectric effects, and their more recently appreciated spin counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, with the discovery of the spin Seebeck effect, 27 a new field of interest, namely spin caloritronics, have started blossoming. [28][29][30][31][32] It transpires that the interplay of charge, heat and spin gives rise to a rich behavior of the thermoelectric coefficients that are now spin-dependent. [33][34][35] In correlated magnetic nanostructures, such as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal gradients at the crucial ferromagnet/non-magnetic metal interface can also drive spin injection in the structure in what is often termed the spin-dependent Seebeck effect (SDSE). [30][31][32][33][34][35][36][37][38][39] The dramatic consequences of the interaction of heat and spin place NLSVs firmly in the growing field of spin caloritronics [40][41][42] that examines coupling between heat and spin in materials and devices.…”
Section: Introductionmentioning
confidence: 99%